President’s Message - Vandale, Tanya (Operating Room Nurses Association of Canada Journal, 2025)
Dear perioperative leaders, As we step into an exciting time for perioperative nursing in Canada, I am thrilled to share some key highlights that showcase ORNAC’s commitment to excellence in patient care, professional growth, and advancing our specialty.